2018
DOI: 10.1080/14756366.2018.1491846
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phenolic glycosides from Betula platyphylla var. japonica on adipocyte differentiation and mature adipocyte metabolism

Abstract: Betula platyphylla var. japonica (Betulaceae) has been used traditionally in Asian countries for the treatment of inflammatory diseases. A recent study has reported a phenolic compound, platyphylloside from B. platyphylla, that shows inhibition on adipocyte differentiation and induces lipolysis in 3T3-L1 cells. Based on this finding, we conducted phytochemical analysis of the EtOH extract of the bark of B. platyphylla var. japonica, which resulted in the isolation of phenolic glycosides (1–4). Treatment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Development of obesity involves two mechanisms: increasing adipocyte size (hypertrophy) and number (hyperplasia), both of which are considered targets for the treatment of obesity . Increase in adipocyte number is achieved through adipocyte differentiation . Currently, adipose tissue is classified into three types, including white (WAT), brown (BAT), and beige.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of obesity involves two mechanisms: increasing adipocyte size (hypertrophy) and number (hyperplasia), both of which are considered targets for the treatment of obesity . Increase in adipocyte number is achieved through adipocyte differentiation . Currently, adipose tissue is classified into three types, including white (WAT), brown (BAT), and beige.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Increase in adipocyte number is achieved through adipocyte differentiation. [5] Currently, adipose tissue is classified into three types, including white (WAT), brown (BAT), and beige. WAT is inherently programmed to store energy in large lipid droplets for later use, and the accumulation of WAT in body fat leads to both hypertrophy and hyperplasia of adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating the anti-cancer effect of platyphyllenone have shown that the compound is capable of inhibiting the proliferation of human breast and lung cancer cells [ 13 , 19 ]. However, in these previous studies, very high concentrations of platyphyllenone (25 µM and 50 µM) were used to investigateits cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…adipocytes yielded Eurycoma longifolia Jack [70]. Two quassinoids from this plant, polymethoxyflavones [72][73][74], pterostilbene [75], arylbutanoid glycosides [76], aculeatin [77], (3, 3-dimethylallyl)halfordinol [78], and arecoline [79]. However, although knowledge of plants containing pro-lipolytic compounds is gradually increasing, the exact mechanisms of action involved require clarification.…”
Section: Screening Of Medicinal Plants For Candidates That Reduce Lipmentioning
confidence: 99%